AN ANALYSIS OF ENGLISH-INDONESIAN TRANSLATING PROCEDURES OF THE MOVIE ENTITLED "BIG HERO 6" BY THREE FREELANCE TRANSLATORS - Humaira, Lidya Annisa (2016)
Penelitian ini bertujuan untuk mengetahui prosedur penerjemahan yang digunakan oleh tiga penerjemah lepas serta menganalisis hasil dari terjemahan itu sendiri. Penelitian ini menggunakan metode deskriptif kualitatif. Terungkap hasil dari prosedur penerjemahan yang dikemukakan oleh Newmark (1988, hal. 81) yang telah digunakan oleh PA adalah transposition (28 kali), literal translation (18 kali), naturalization dan paraphrase (15 kali), reduction (10 kali), transference (9 kali), dan expansion (5 kali). Sementara itu, dalam terjemahan GD, penggunaannya adalah transposition (28 kali), literal translation (18 kali), naturalization (12 kali), transference (11 kali), reduction (10 kali), paraphrase (8 kali), dan expansion (5 kali). Di samping itu, dalam terjemahan LG, penggunaannya adalah transposition (35 kali), literal translation (16 kali), transference (14 kali), naturalization (13 kali), reduction (9 kali), expansion dan paraphrase (5 kali). Kualitas dari semua terjemahan telah memenuhi kriteria dari terjemahan yang baik berdasarkan teori yang dikemukakan oleh Newmak (1988) dan Larson (1984). Ini dikuatkan oleh hasil dari wawancara beberapa responden yang kompeten di bidang ini. Hasil yang terungkap adalah seluruh responden mengemukakan bahwa seluruh terjemahan telah memenuhi kriteria terjemahan yang baik. Kata kunci: terjemahan, menterjemahkan, prosedur, kualitas, subtitle This research aims to find out the translating procedures that three freelance translators used and analyzing the quality of the translations. This research uses qualitative descriptive method. The result revealed the translating procedures used in the PA's translation proposed by Newmark (1988, page 81) were transposition (28 times), literal translation (18 times), naturalization and paraphrase (15 times), reduction (10 times), transference (9 times), and expansion (5 times). Meanwhile, in GD's translation, the usage are transposition (28 times), literal translation (18 times), naturalization (12 times), transference (11 times), reduction (10 times), paraphrase (8 times), and expansion (5 times). Beside, in LG's translation, the usage are transposition (35 times), literal translation (16 times), transference (14 times), naturalization (13 times), reduction (9 times), expansion and paraphrase (5 times). The quality of the translations are fulfilled by the criteria of a good translation based on the framework proposed by Newmark (1988) and Larson (1984). This is reinforced by the results of interviews of some of the respondents who are competent in their field. The results revealed that all respondents expressed that the translations are fulfilled the criteria of a good translation. Keywords: translation, translating, procedure, quality, subtitle